The Assessment of Inequality on Geographical Distribution of Non-Cardiac Intensive Care Beds in Iran - A Ameryoun; M Meskarpour-Amiri; M Lorgard Dezfuli-Nejad; HR Khoddami-Vishteh; Sh Tofighi (Tehran University of Medical Sciences, 2011)
Background: The purpose of the present study was to evaluate the inequality of geographical distribution of non-cardiac intensive care beds in Iran using the Gini coefficient. Methods: The population information of Iran's provinces in 2006 was obtained from The Statistical Center of Iran and the number of non-cardiac intensive care beds (including ICU, PostICU and NICU beds) in all provinces was taken from published information of Ministry of Health and Medical Education of Iran in the current year. The number of beds per 100,000 populations of each province and the Gini coefficients for each bed were calculated. Results: Iran's population was 70,495,782. The total number of ICU, PostICU and NICU beds were 3720, 291 and 1129, respectively. Tehran had the highest percentage of each bed among all provinces. The number of each bed was 5.3, 0.4 and 1.6 per 100,000 populations of country, respectively. The calculated Gini coefficients for each bed were 0.17, 0.15 and 0.23, respectively. Conclusion: The findings of this study showed that, according to the Gini coefficients, non-cardiac intensive care beds have an almost equal geographical distribution throughout the country. However, the numbers of beds per population are less than other countries. Since such studies can be used as a base for health systems planning about correction of inequality of health services distribution, similar studies in other health care services are recommended which can be conducted at the national or provincial level.